Probing and manipulating the gut microbiome with chemistry and chemical tools - Pavan K. Mantravadi; Basavaraj S. Kovi; Sabbasani Rajasekhara Reddy; Ganesh Pandian Namasivayam; Karunakaran Kalesh; Anutthaman Parthasarathy (Gut Microbiome)
The human gut microbiome represents an extended “second genome” harbouring about 1015 microbes containing >100 times the number of genes as the host. States of health and disease are largely mediated by host–microbial metabolic interplay, and the microbiome composition also underlies the differential responses to chemotherapeutic agents between people. Chemical information will be the key to tackle this complexity and discover specific gut microbiome metabolism for creating more personalised interventions. Additionally, rising antibiotic resistance and growing awareness of gut microbiome effects are creating a need for non-microbicidal therapeutic interventions. We classify chemical interventions for the gut microbiome into categories like molecular decoys, bacterial conjugation inhibitors, colonisation resistance-stimulating molecules, “prebiotics” to promote the growth of beneficial microbes, and inhibitors of specific gut microbial enzymes. Moreover, small molecule probes, including click chemistry probes, artificial substrates for assaying gut bacterial enzymes and receptor agonists/antagonists, which engage host receptors interacting with the microbiome, are some other promising developments in the expanding chemical toolkit for probing and modulating the gut microbiome. This review explicitly excludes “biologics” such as probiotics, bacteriophages, and CRISPR to concentrate on chemistry and chemical tools like chemoproteomics in the gut-microbiome context.